2004
DOI: 10.1203/01.pdr.0000121197.24154.82
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation, Inflammation, and the Risk of Neonatal White Matter Damage

Abstract: Indicators of coagulation activation are sometimes increased in the blood of newborns and adults who have a systemic inflammatory response. These coagulation factors have the ability to exacerbate inflammation, which in turn can promote coagulation. Therapies directed solely at coagulation factors and therapies directed solely at inflammation factors have not proved effective in reducing mortality in adults with a systemic inflammatory response syndrome and multiorgan dysfunction (SIRS/MOD). On the other hand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 81 publications
0
66
0
3
Order By: Relevance
“…The interaction of inflammation and coagulation is apparently important in the genesis of CP in very preterm, and perhaps also in more mature, infants (8). Some of these genes are also involved in anti-oxidant and anti-excitotoxic defense.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of inflammation and coagulation is apparently important in the genesis of CP in very preterm, and perhaps also in more mature, infants (8). Some of these genes are also involved in anti-oxidant and anti-excitotoxic defense.…”
Section: Discussionmentioning
confidence: 99%
“…Mature oligodendrocytes become abundant after term. Two major causes are generally considered to be responsible for perinatal white matter injury: cerebral ischemia/reperfusion in the premature infant, combined with the propensity for impaired vascular autoregulation (Menke et al, 1997;Volpe, 1998) and bacterial infection in the mother and/or fetus that triggers a cytokine response in the fetal brain (Kinney et al, 2004;Leviton and Dammann, 2004). In the past 10 years, there has been no improvement in the neurodevelopmental outcome of premature infants (Hamrick et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Recent studies have identified perinatal infection and inflammation as risk factors for cerebral white matter damage. [7][8][9][10] Preterm infants born to mothers with clinical or histologic chorioamnionitis are at risk for adverse neurodevelopmental outcomes, with a particularly high risk of cerebral palsy. 11 Very preterm infants have a high risk of multiple infections between birth and hospital discharge.…”
mentioning
confidence: 99%